IMPACT OF SMARTPHONE USAGE ON SOCIAL BEHAVIOR OF ELEMENTARY SCHOOL STUDENTS: ANALYSIS OF EFFECTS AND CONTRIBUTING FACTORS - Rahmi Rais; Sri Hardiyanti Lukman (P3M Stia Al Gazali Barru and Meraja media, 2024)
[Full Paper] to pdf Copyright (c) 2024 Meraja journal